Embalagens de medicamentos: diretrizes para o desenvolvimento - Lucio, Cristina do Carmo [UNESP] (2013)
The medidines are essential in the heath system, with great economic and social importance. Considering the increase in the consumption of medicines in the world, being the Brazil one of the top ten pharmaceutical markets, and the increase in the elderly populaition, its primary user, it is important to know the interface aspects of these packages, as well as understand the aging process and skills and difficulties in handling of their target. There are many of these packages, and many have several problems, from low readability, security issues, which is exarcebated when they are used by the elderly or people with poor manual dexterity or with health problems such as rheumatoid-arthritis. This research aims to generate parameters for regulation and practical application in the packaging industry of medicines and, therefore, were required several theoretical and market research, to understand the interface aspects of these products with their users. Thereby, initially it's presents a comprehensive review of the literature, which includes skills and difficulties in handling products for different users, with emphasis on the elderly, as well as indispensable elements for setting the packaging for medicines, as medicines with interface structural materials, standards, laws and regulations dealing with medicines. To confirm the hypothesis that there are problems at the interface of these packages, the methodologies and the results analysed and discussed the approaches with users, as well as the usability evaluation. After all the data analyzed and discussed in the literature, it was possible to set parameters for the development of new packaging, among them, the ampaule, the tube of ointment, the child protection packaging, the drapper, battles for syrup and bottles for pills and the secondary packaging